Five new species of the genus Tetroxyrhina Hendel from China (Diptera, Lauxaniidae) - Shi, Li; Gaimari, Stephen D.; Yang, Ding (Zootaxa, 2017)
Five species of the genus Tetroxyrhina Hendel from China are described as new to science: Tetr. dashahensis sp. nov., Tetr. dentata sp. nov., Tetr. jinpingensis sp. nov., Tetr. menglunensis sp. nov. and Tetr. tengchongensis sp. nov., and the species Tetr. sauteri (Hendel), also from China, is redescribed. The genitalia of these species are illustrated and described. Trigonometopus alboapicalis Shatalkin, is synonymized under Tetr. sauteri, syn. nov. A key to separate all species of the genus is provided, along with nomenclatural details for all species, and photographs of all primary type specimens.